Determining the Attenuation Factor in Molecular Wires Featuring Covalent and Noncovalent Tectons - Vela, Sonia; Bauroth, Stefan; Atienza, Carmen; Molina-Ontoria, Agustin; Guldi, Dirk Michael; Martin, Nazario (Angewandte Chemie International Edition, 2016)
Hybrid covalent/supramolecular porphyrin–fullerene structures were synthesized as highly efficient molecular wires with a remarkably low attenuation factor (β=0.07±0.01 Å−1). Hydrogen-bonding interactions and p-phenylene oligomers of different lengths are responsible for efficient electron transfer in the molecular wires.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electron transfer; fullerenes; hydrogen bonds; molecular wires; porphyrinoids